Correlating Schizophrenia with DRD3 Ser9Gly or HTR2 Receptor Gene Variants by using RFLP Method - Mohammed Ayyed Najm1 , Zeina S. M. Al –Hadeithi2 , Ali Talib Abid Salih3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Genetic polymorphism in many candidates associated with psychiatric disorder and Schizophrenia (SCZ). The current research is directed to see if the polymorphisms of Dopamine Receptor D3 (DRD3) or of the 5-Hydroxytryptamine Type 2A (HTR2A) genes is related to SCZ patients. From those admitted to Al Rasheed Hospital, fifty patients with SCZ (half of them are males and the other half are females), in addition to control group (25 healthy individuals) were included in this study. Blood samples from each individual in both, healthy and control groups were collected, DNA was extracted. Specific primers for exon1 and another for exon 2 have been used to amplify the genes of DRD3 receptor and HTR2A. The data generated in this study indicated significant positive association between T102C polymorphism of HTR2A A1804G transition and DRD3 gene sequence, that resulted in the substitution of Ser9Gly amino acid Iraqi SCZ patients.